2018
DOI: 10.1037/xhp0000457
|View full text |Cite
|
Sign up to set email alerts
|

Explicit goal-driven attention, unlike implicitly learned attention, spreads to secondary tasks.

Abstract: To what degree does spatial attention for one task spread to all stimuli in the attended region, regardless of task relevance? Most models imply that spatial attention acts through a unitary priority map in a task-general manner. We show that implicit learning, unlike endogenous spatial cuing, can bias spatial attention within one task without biasing attention to a spatially overlapping secondary task. Participants completed a visual search task superimposed on a background containing scenes, which they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…Stimuli Our paradigm was adapted from Addleman et al (2018). Throughout the experiment, a red fixation dot subtending 0.15°visual angle remained in the display's center.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimuli Our paradigm was adapted from Addleman et al (2018). Throughout the experiment, a red fixation dot subtending 0.15°visual angle remained in the display's center.…”
Section: Methodsmentioning
confidence: 99%
“…For example, LPL acquired in letter search transfers to a similar search task for a small arrow superimposed on natural scenes (Salovich, Remington, & Jiang, 2017). Conversely, no transfer was observed from letter search to a letter foraging task that required selection of any one of many target letters to receive a reward (Jiang, Swallow, Won, Cistera, & Rosenbaum, 2015), or from letter search to scene memory (Addleman, Tao, Remington, & Jiang, 2018). Unfortunately, these studies' two-phase designs, in which participants trained on one task and then completed a second task, prevent conclusions about whether LPL yields baseline shifts of attention; because participants knew the upcoming task, they could adjust their attentional set for each task.…”
mentioning
confidence: 97%
“…Moreover, the higher frequency of letter trials than scene trials may have further incentivized the deployment of attention in anticipation of letter trials, but we found no evidence of this effect. LPL benefitted only letter search, indicating that it results in an on-line search habit initiated after stimuli appear (Addleman et al, 2018;Jiang, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Our paradigm was adapted from Addleman et al (2018). Throughout the experiment, a red fixation dot subtending 0.15° visual angle remained in the display's center.…”
Section: Stimulimentioning
confidence: 99%
“…Such conflict between long-term encoding of pair-response contingencies and the response rule currently in working memory suggests that there may be a cost to memory incurred with the cognitive flexibility provided by structure building. One question that arises from these data is whether this cost to memory is observed only for the type of structure building assessed in our study or generalizes to scenarios when selective attention more readily biases control processing (e.g., Addleman, Tao, Remington, & Jiang, 2018).…”
Section: Relationship To Control-learningmentioning
confidence: 89%